Synthesis and Characterization of PVA-Enzyme/GA/PANI-HCl Indicator Membrane Electrodes; PANI-p-toluentsulfonic acid/PVC-KTpClPB-o-NPOE, SEM-EDX, XRD and FTIR Analysis - Abd Hakim S; Martha Rianna; Jane Elnovreny (Postgraduate, University of Mataram, 2023)
Research has been carried out on the indicator electrode PVA-Enzyme/GA-2.9%/PPy+Sulfonic Acid/PVC-KTpClPB-o-NPOE, the amorphous spectral pattern is greatly reduced for variations of the enzyme 0.6 g in 0.5 mL (50% water + 50% alcohol) . PVA-Enzyme/GA-2.9%/PPy+Sulfonic Acid/PVC-KTpClPB-o-NPOE indicator electrode, denoted As-1. Analysis of the linear curve of the As-1 sample with a sensitivity of 41.56 mV/decade, a detection range of 10-4 - 10-1 M and a detection limit of 10-4 M, R2 = 97.51 %. To increase the sensitivity, detection range, detection limit and confidence level of R2. Indicator electrodes were made with variations of the urease enzyme on PVA and o-NPOE variations on PVC-KTpClPB 61% and 66% and replacement of PANI conductive polymer. PANI conductive polymer was dissolved in hydrochloric acid HCl denoted PANI-HCl and p-toluensulfonic acid is denoted by PANI-p-toluensulfonic acid. SEM analysis shows that the morphology of S3 is greater than that of S2. Analysis of the cps/eV EDX voltage range is greater than S3 to S2. Analysis of the XRD intensity spectrum pattern on the 2theta diffraction angle is greater than S3 to S2. Likewise, the analysis of the %Transmittance FTIR spectrum pattern for wave numbers S3, S6, S8 is higher than S2. The best result according to material analysis is S3.Â